Corporate Entrepreneurship Managers' Project Terminations: Integrating Portfolio–Level, Individual–Level, and Firm–Level Effects. (July 2016) - Behrens, Judith; Patzelt, Holger
Corporate entrepreneurship managers often need to terminate projects to maximize their innovation portfolios' commercial prospects. Drawing on the attention–based view of the firm, we develop a model for how past project failure experience, the firm's growth rate, and their hierarchical level impact managers' attention to a project's fit with the corporate portfolio strategy and the balance of the portfolio when terminating projects. Using data from a conjoint study with 6, 944 assessments of project terminations made by 217 managers, we provide insights into corporate entrepreneurship decision making and how portfolio–level, individual–level, and firm–level aspects interact in explaining project termination.